Coupling Analysis of Water Injection Softening-Precursor Information Prediction of Coal-Rock Mass Based on Energy Conduction. (21st June 2022) - Xu, Haidong; Lai, Xingping; Cao, Jiantao; Xu, Huicong; Zhang, Shuai
Abstract : To further refine the rationality of pressure relief measures, the pressure relief measures are transformed from engineering scale to laboratory scale. In this paper, the static load is applied by uniaxial compression, and the difference in the energy evolution process of loaded coal samples is compared using pressure relief at an indoor scale. The test results show that the pressure relief state of water injection can meet the conditions well and reduce the impact tendency of the whole coal samples. In addition, try to analyze the reasons why it is difficult to accurately predict the formation of rockburst in coal roadway by analytical means. Due to the special structure of coal, it can be found that both natural and saturated conditions can meet the conditions in the state of water injection and pressure relief, while in the dry state, the conditions cannot be met; that is, the precursor signals of disaster cannot be accurately picked up, and finally, the failure of coal samples cannot be accurately predicted. However, on the laboratory scale, the natural coal samples are in the state of adsorption in the air after sampling, and the coal bodies near the deep underground working face tend to have low water content due to the development of pores and fissures and the influence of self-weight of mining disturbance. The research in this paper provides theoretical support for the subsequent determination of pressure relief parameters, and the related research conclusions are of great significance.